Influência do porta-enxerto, da configuração de extração e do período de maturação no teor de limonina e na aceitação sensorial do suco de laranja Pêra-Rio - Barbosa, Eliane [UNESP] (2014)
The aim of this work was to gather information about limonoids, specially limonin, to understand the causes of their formation in orange juice, to develop and to validate an analytical method to determinate limonin in orange juice, to evaluate the influence of rootstock, extractor setting and maturity on the limonin level, the physico-chemical characteristics, the sensory acceptance, the intensity of sweet, sour and bitter tastes, the scale of the ideal for bitter taste and purchase intent of Pêra-Rio orange juice, and also to determine the threshold of limonin in orange juice from Pêra-Rio variety. Validation of the analytical method involved calibration curve, linearity, precision, accuracy, limit of detection and limit of quantification. Regarding to the physico-chemical characteristics of orange juice, soluble solids, titratable acidity, ascorbic acid and total sugars, pH and ratio were evaluated. Sensory acceptance of orange juice evaluated appearance, aroma, overall impression, flavor, texture and aftertaste at the beginning and ending of harvest. The intensity of sweet, sour and bitter tastes, the scale of the ideal for bitter taste of orange juice, and the purchase intent at the beginning and ending of harvest were also evaluated. Limonoids are highly oxygenated triterpenoids present in Citrus, in different parts of the plant as aglycones and/or glucosides. Limonoids contribute to the development of bitterness in citrus juice, with a negative impact on the quality of the juice. Limonin, the main limonoid responsible for bitterness in orange juice, is not present in the in natura fruit, but is formed from the extraction of the juice. The amount of limonin in the juice is influenced by the type of rootstock and variety of orange, mainly due to the maturation period. The developed and validated method was used to determine limonin in orange juice with precision and accuracy. Wide linear range was obtained (0.410-61.5 μg.mL-1), ...